Exploring some Libyan EFL Undergraduate Students' Perceptions of Undertaking Graduation Projects - Aiesha Ali E Emhammed; Hind Mohammed; Zamzam Ahmed (Abhat Journal, 2023)
This study explored Libyan undergraduate students' perceptions of undertaking their graduation projects at the department of English at Sirte University. 9 undergraduate students who were in the process of conducting their projects formed the sample of the study. The multiple semi-structured interviews used in order to gather the data which was analyzed thematically. The results of the present study revealed that students had difficulties while conducting their graduation projects. The most identified challenges were related to the academic writing aspect, working within groups, data collection, applying research methods, and insufficient time. However, for most of the students, the experience with the supervisor was positive. Thus, at the end of their graduation projects, students found that it was a challenging but worthwhile learning experience. Finally, the findings of this study have vital implications for improving the process and quality of graduation projects of the English Department students at Sirte University.